Reconstructing the history of helminth prevalence in the UK - Hannah Ryan; Patrik G Flammer; Rebecca Nicholson; Louise Loe; Ben Reeves; Enid Allison; Christopher Guy; Inés Lopez Doriga; Tony Waldron; Don Walker; Claas Kirchhelle; Greger Larson; et al. (Public Library of Science (PLoS), 2022)
Intestinal helminth parasites (worms) have afflicted humans throughout history and their eggs are readily detected in archaeological deposits including at locations where intestinal parasites are no longer considered endemic (e.g. the UK). Parasites provide valuable archaeological insights into historical health, sanitation, hygiene, dietary and culinary practices, as well as other factors. Differences in the prevalence of helminths over time may help us understand factors that affected the rate of infection of these parasites in past populations. While communal deposits often contain relatively high numbers of parasite eggs, these cannot be used to calculate prevalence rates, which are a key epidemiological measure of infection. The prevalence of intestinal helminths was investigated through time in England, based on analysis of 464 human burials from 17 sites, dating from the Prehistoric to Industrial periods. Eggs from two faecal-oral transmitted nematodes (Ascaris sp. and Trichuris sp.) and the food-derived cestodes (Taenia spp. and Diphyllobothrium latum syn Dibothriocephalus latus) were identified, although only Ascaris was detected at a high frequency. The changing prevalence of nematode infections can be attributed to changes in effective sanitation or other factors that affect these faecal-oral transmitted parasites and the presence of cestode infections reflect dietary and culinary preferences. These results indicate that the impact of helminth infections on past populations varied over time, and that some locations witnessed a dramatic reduction in parasite prevalence during the industrial era (18th-19th century), whereas other locations continued to experience high prevalence levels. The factors underlying these reductions and the variation in prevalence provide a key historical context for modern anthelmintic programs. Author summary Parasitic worms (helminths) cause many health problems in poorer countries, particularly those in tropical and sub-tropical regions. In modern Europe these infections are very rare and mostly found in those travelling from endemic areas but this wasn't always the case. Archaeological studies have detected eggs of parasitic helminths in numerous European sites. Key questions include how prevalent these infections were in past communities and whether (or when) these patterns changed over time? This paper addresses both of these questions using a large number of single grave samples from archaeological sites in England dating between Prehistoric and Industrial periods. Helminth infections were detected across all periods but the overall prevalence rates changed over time, being highest in the Roman and Late-Medieval periods. The Industrial period was interesting in that two of the three sites contained very few (or no) parasites whereas the third, London, contained high levels of infection. We discuss factors that may have contributed to the changing parasite landscape and how understanding these factors may influence efforts to control helminth infections in modern endemic areas.